An analysis of the changes in the 2017 version of ISO 17025 and INACAL directives and its efect on peruvian accredited laboratories - Gutiérrez Lara, Ricardo (2023)
This paper reviews the requirements of the new versión of the standard ISO/IEC 17025:2017 General Requirements for the Competence of Testing and Calibration Laboratories, which has been totally adopted as the Peruvian technical standard NTP-ISO/IEC 17025:2017, “Requisitos generales para la competencia de los laboratorios de ensayo y calibración” and relates these requirements to the directives issued by the Peruvian National Institute of Quality (INACAL), as some of them make some requirements more demanding and/or more precise, and clear, for their application by INACAL accredited laboratories. This paper aims at being a quick guide for helping in the implementation of NTP-ISO/IEC 17025:2017, keeping in mind, at the same time, the directives of INACAL for accreditation of laboratories.